Lower phase angle as a marker for poor prognosis in patients with chronic kidney disease: a cohort study - Chen, Yi-qin; Chen, Hui-fen; Han, Yan; Shen, Yu-han; Zhang, Yi-dan; Fu, Li-zhe; Tang, Fang; Liu, Xu-sheng; Wu, Yi-fan (Frontiers in Nutrition, 2025)
ObjectivePhase angle (PhA) obtained through bioimpedance analysis has been linked to mortality and malnutrition in dialysis patients. However, it remains unclear whether PhA is associated with renal prognosis in non-dialysis CKD patients.MethodsTwo thousand two hundred two CKD patients were enrolled in the SMP-CKD cohort, Guangdong Provincial Hospital of Traditional Chinese Medicine from July 1, 2015 to May 31, 2024. Participants undertook bioimpedance measures, and the correlation between PhA and renal endpoint was analyzed. Analytical approaches include Cox proportional hazards analysis and group-based trajectory modeling. Composite outcome is defined as the first occurrence of >30% decline or <5 mL/min/1.73m2in eGFR, doubled of SCr from the baseline, initiation of continuous dialysis therapy or receipt of a kidney transplant, or all-cause mortality.ResultsDuring a mean follow-up of time 2.5 years, 570(25.9%) participants reached the composite endpoint. In the multivariable Cox regression model, subjects belonging to higher quartiles of phase angle presented with a decreased risk of poor prognosis, showing 29 and 38% risk reductions in Q3 (aHR 0.71, 95%CI 0.55–0.93) and Q4 (aHR 0.62, 0.45–0.85) versus Q1 (both p < 0.05). When modeled in 2 groups according to the turning point of 5.0°, the adjusted hazard ratios (aHRs; 95% confidence intervals [CIs]) for broad-PhA group was 0.77(0.63, 0.95) compared with narrow-PhA group. The group-based trajectory modelling (GBTM) identified 4 trajectories, and the beneficial association remained consistent, with aHR (95% CIs) for group 2, group 3, group 4 were 0.69 (0.50–0.95), 0.59 (0.39–0.90), 0.47 (0.24–0.93), respectively, compared with group 1.ConclusionPhase angle could be useful in determining nutritional status of CKD patients, lower phase angle is an independent risk factor for poor prognosis in CKD patients.